Wind and water : Mauritania' s new agricultural associates - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
An anti-desertification programme has just been launched by the government of Mauritania. It will include the installation of windpumps for irrigation and the watering of animals as well as the development of a cultivation zone protected by a...